Holistic Education in the Implementation of Islamic Value Morality in Inclusion Schools in The Covid 19 Pandemic Period - Ayu Faiza Algifahmy (Universitas Islam Sultan Agung, 2022)
This study aims to find out in depth about holistic education in the application of Islamic value morality in inclusive schools during the Covid 19 pandemic. This research is a field research (field research) using a qualitative descriptive approach and interview methods. The results of this study are that with the limitations of online learning that was carried out during the Covid 19 pandemic, Islamic value morality becomes a unity seen in the existing holistic education process, in the form of the development of social, academic, physical, and religious potential. The role of the teacher is a central part in this matter, role theory alone is not enough, but how can teachers touch the hearts of students so that the goals of education can be achieved thoroughly, and return to human nature and can apply Islamic principles in themselves, learning activities in the classroom, and social processes in the environment.